If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9k + 27 = 0 Reorder the terms: 27 + 9k = 0 Solving 27 + 9k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 9k = 0 + -27 Combine like terms: 27 + -27 = 0 0 + 9k = 0 + -27 9k = 0 + -27 Combine like terms: 0 + -27 = -27 9k = -27 Divide each side by '9'. k = -3 Simplifying k = -3
| 2+3(-1)/6+(-7)+1= | | 9x+15=9x-15 | | 7+2s-5=8s+20-4s | | 4600=k(30) | | 4v+23v+28=0 | | 2s+8l=120 | | x^4-5x^3-13x^2-7x=0 | | 14-2(3p+1)=5x-(x+21) | | 14-(-2)=10 | | 85+110+12x-1+11x+5=360 | | x^2-9x+20.45=0 | | x+x+0.0+x+010+0.63=10.28 | | -8(2k-6)=16 | | x=10.4+(9.8)(1.7) | | 3c+23c+40=0 | | 99-99=0 | | 4x-2(-4)=12 | | 2(t-3)+8t=5(2t+3)-11 | | 45s^2+100st+55t^2=0 | | 4(m-3)=3m+5 | | 2(x+3)+xy=4-(x+13)+xy | | -16w^2+36w+70=0 | | -5x-2y=-16 | | 44.59=9g+3.82 | | 1.4t=56 | | 4(-4)-2y=12 | | 1.44g-3=0.60 | | 7x=31+-2y | | 6(5-2g)-3(-p+7)= | | 6(2x+9)=(6x+12) | | 4v^2+24v+27=0 | | -44-6x=-x+16 |